Comparative study of combustion and thermal performance in a swirling micro combustor under premixed and non-premixed modes. (September 2019) - Yang, Xiao; Zhao, Lei; He, Zhihong; Dong, Shikui; Tan, Heping
Highlights: A novel swirling micro combustor for MTPV system is proposed. Performance of premixed and non-premixed combustion modes is reported. Premixed mode has better flame stability. Non-premixed combustion is better for MTPV system at low hydrogen mass flow rate. Thermal performance is improved by premixed mode at low hydrogen/air equivalence ratio. Abstract: A swirling micro combustor fueled by hydrogen/air has been proposed based on the concept of swirling flow stabilization. The effects of premixed and non-premixed combustion modes on the combustion efficiency, flame stability, and thermal performance of the micro combustor at various hydrogen/air mass flow rates and equivalence ratios are discussed and compared. The results show that premixed mode has a lower flame location than non-premixed mode, and the flame location of non-premixed mode is more susceptible to changes of hydrogen/air mass flow rate and equivalence ratio than premixed mode. When the hydrogen mass flow rate is lower, the non-premixed mode is more suitable for micro thermophotovoltaic (MTPV) system because the wall temperature is more uniform. However, the premixed mode has a higher and more uniform wall temperature distribution at high hydrogen mass flow rate. Moreover, the hydrogen/air equivalence ratio has a significant effect on the thermal performance in the swirling micro combustor, and the advantage of a high and uniform wall temperature distribution of premixed mode is more obvious at small equivalence ratio. This work provides a reference for the choice of micro combustor combustion modes under different hydrogen/air mass flow rates and equivalence ratios in the MTPV system.